Successful Management of Post-Excisional Biopsy Dehisced Wound with 1% Framycetin Sulphate and Ozonated Oil Adjuvant: A Case Report - Mawu, Ferra Olivia; Sondakh, O. Reymond L.; Tampi, Joan Alexandra; Christopher, Paulus Mario (Faculty of Medicine, Universitas Diponegoro, 2025)
Background: Wound dehiscence is wound edges separation due to disrupted wound healing. Wound dehiscence is a complication in 8% of dermatologic surgeries. In this case, secondary infection of the wound occurred, 1% framycetin sulphate tulle was then chosen to interfere microbial protein synthesis, combined with ozonated oil as adjuvant therapy. Ozone oxidizes bacterial phospholipids and lipoproteins, promotes local tissue metabolism, stimulates fibroblast proliferation, facilitates collagen fiber formation, and supports angiogenesis. This case report described a post-excisional biopsy dehisced wound that was treated with 1% framycetin sulphate tulle and ozonated oil, and this case is the first to report a successful management of post-excisional biopsy dehisced wound with ozonated oil as adjuvant. Case Presentation: An 11-year-old female was brought with a purulent wound on her head post-excisional biopsy. Examination of the parietal region showed a solitary ulcer, 1 cm in diameter, irregular edge, granulated tissue base, serous exudate, crusting, edema, and pus. Treatment was 0.9% NaCl compress, 1% framycetin sulphate tulle, and ozonated oil once weekly. Evaluation on day 21 showed ulcer size reduction and on day 28, ulcer turned into a scar, treatment was continued with mometasone 0.1% cream. Day 86 showed secondary cicatricial alopecia. Complications of a wound in hair-bearing area can occur, in this case, secondary cicatricial alopecia.Conclusion: This paper highlights the utilization of ozonated oil as an adjuvant therapy for a favorable outcome in wound healing.